Tax E-filing in Jordan: A Conceptual Model - et al., Eyad M. Malkawi (International Journal of Advanced Science and Technology, 2020)
Tax e-filing will be one of the e-government services that will be picking up importance for opento perform their responsibility to the nation through expense payment. Despite the quick reception of efiling in Jordan , the e-filing system will be still unreliable especially at peak period which lead to highlevel of danger perceived by taxpayers. This paper proposes a framework that incorporates the hugeeffect of performance danger, which will be a critical perceived hazard facet, on charge e-filingappropriation in Malaysia. In this paper, the framework likewise places the perceived danger andperformance chance inside the Technology Acceptance Model (TAM) inside the e-filing context. This modelwill serve as a useful guideline not for devising strategies to promote e-government services,especially charge e-filing service however likewise to improve the performance of the e-filing system.